Pengaruh Disiplin Kerja Dan Lingkungan Kerja Fisik Terhadap Produktivitas Karyawan Pada PT The Body Shop Indonesia Di Tangerang Selatan - Ayu Oktavia; Raden Yeti Sumiaty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The aim of this research is to determine the effect of work discipline and Physical work environment on employee productivity at PT The Body Shop Indonesia in South Tangerang partially and simultaneously. The research method used is quantitative. The sampling technique applied is saturated sampling, resulting in a total sample of 63 respondents. Data analysis includes validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression tests, simple linear regression tests, correlation coefficient analysis, coefficient of determination analysis, partial hypothesis testing (t-test), and simultaneous hypothesis testing (F-test). The results of this Work discipline and Physical work environment simultaneously have a significant effect on employee productivity, as shown in the regression equiation Y = 13.538 + 0.259 X1 + 0.346 X2. study indicate that work discipline has a significant effect on employee productivity, with a coefficient of determination of 34.6%. The hypothesis test results show that the t-value is greater than the t-table value (5.685 > 1.670). The Physical work environment also has a significant effect on employee productivity, with a coefficient of determination of 37.5%, and the hypothesis test results show that the t-value is greater than the t-table value (6.048 > 1.670). The coefficient of determination is 40.4%, while the remaining 59.6% is influenced by other factors. The hypothesis test results show that the F-value is greater than the F-table value (20.344 > 2.76). Keywords: Work Discipline, Physical Work Environment, Employee Productivity